2014
DOI: 10.1007/s12013-014-0118-y
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Transplantation from Pediatric Donors in a Single Chinese Center

Abstract: To report clinical outcomes of kidney transplantation from pediatric brain and cardiac death donors (DBCD) in a single Chinese center and to investigate its feasibility to expand organ donor pool. 18 recipients, transplanted between August 2011 and October 2013 in the First Affiliated Hospital of Zhengzhou University, receive a single graft from DBCD donors age ranged from 1.5 to 13 years old. Renal function expressed as serum creatinine, blood urea nitrogen as well as eGFR values at 1, 2 weeks as well as 1-, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Additional recent studies of clinical outcomes have shown that pediatric DBCD kidney donation for transplant is also feasible [5]. Furthermore, the DBCD program adheres to the guiding principles of the World Health Organization, and is compliant with the Declaration of Istanbul.…”
Section: Introductionmentioning
confidence: 99%
“…Additional recent studies of clinical outcomes have shown that pediatric DBCD kidney donation for transplant is also feasible [5]. Furthermore, the DBCD program adheres to the guiding principles of the World Health Organization, and is compliant with the Declaration of Istanbul.…”
Section: Introductionmentioning
confidence: 99%
“…However, an imbalance between donors and potential recipients has been aggravated by the rapid growth of ESRD patients on the waiting list, which has outpaced the collection of donor kidneys. Nonetheless, the donor pool had expanded due to an increase in the number of pediatric donors over the past few years (2)(3)(4)(5)(6)(7)(8). This expansion alleviates the conflict between the high demand among ESRD patients and the lack of donor organs.…”
Section: Introductionmentioning
confidence: 99%
“…A c c o r d i n g t o t h e O r g a n P r o c u r e m e n t a n d Transplantation Network (OPTN) and the Australia and New Zealand Organ Donation Registry (ANZOD), the proportion of pediatric donors has exceeded 10%, and the overall prognosis is also satisfactory (2,(7)(8)(9)(10)(11)(12)(13). Moreover, studies indicated that the prognosis of kidneys from pediatric donors is comparable to or better than that of adult donors (14,15).…”
Section: Introductionmentioning
confidence: 99%